Properties of soils derived from some metamorphic rocks in Peninsular Malaysia - Zauyah, S. (Universiti Pertanian Malaysia, 1988)
The morphological, physical, chemical, mineralogical and micro morphological properties of five soils developed over some metamorphic rocks (quartz-mica schist, phyllite, graphitic sericite schist, amphibole schist and serpentinite) were examined. These properties were found to be influenced by the parent materials. Soils developed over rocks with low amounts of weather able minerals (ferromagnesian) and low total iron content (quartz-mica schist, sericite schist and phyllite) are reddish yellow, have silty clay textures and blocky structures, low CEC and base saturation and low free iron oxide content. The diagnostic horizon is argillic. Soils formed over rocks with high amounts of weatherable minerals (amphibole schist and serpentinite) are red to brown, have clayey textures, granular structures, low CEC, moderate base saturation and high free iron oxide content. The diagnostic horizon is toxic. Pedofeatures in the first group of soils are dominated by clay and excremental infillings whilst in the second group, only excremental infillings are dominant.